1990
DOI: 10.1088/0953-8984/2/6/020
|View full text |Cite
|
Sign up to set email alerts
|

An electron spin resonance study of thermoluminescence mechanisms in CaSO4:Dy

Abstract: Mechanisms of thermoluminescence (TL) in CaSO4:Dy are studied using electron spin resonance (ESR) in single-crystal samples. The ESR analysis indicates the presence of several variations of a distorted SO4- centre locally stabilised by a nearest neighbour Ca vacancy. This centre's structure, which has not been reported previously, relates to several centres observed in this system and could also explain results in related compounds. The presence of the Dy impurity, which increases the concentration of Ca vacan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Mere presence of Eu 3+ emission (in peaks III and V) does not support model I automatically. For example, an earlier study [6] luminescence when the irradiation temperature was increased from 350 to 450 K. But the above redox model predicts an increase in Eu 2+ luminescence during the readout of peak IV at 400 K. The energy transfer model [13] is, however, more consistent with these results. Table 1 shows that the X-ray induced TSL emission spectra of Da-II also shows more or less a similar behaviour to Y-700, the only difference being that the Eu 2+ emission could not be seen at all in peaks III and V of Da-II.…”
Section: X-ray Induced Tslmentioning
confidence: 79%
See 2 more Smart Citations
“…Mere presence of Eu 3+ emission (in peaks III and V) does not support model I automatically. For example, an earlier study [6] luminescence when the irradiation temperature was increased from 350 to 450 K. But the above redox model predicts an increase in Eu 2+ luminescence during the readout of peak IV at 400 K. The energy transfer model [13] is, however, more consistent with these results. Table 1 shows that the X-ray induced TSL emission spectra of Da-II also shows more or less a similar behaviour to Y-700, the only difference being that the Eu 2+ emission could not be seen at all in peaks III and V of Da-II.…”
Section: X-ray Induced Tslmentioning
confidence: 79%
“…The generally held view is that during TSL readout of RE doped CaSO 4 phosphors, it is the holes and not electrons that are released which on recombination with the electrons trapped elsewhere give rise to TSL emission following X-or g-irradiation. In this model, denoted as model II first proposed by Huzimura et al [12] and later on expanded by Morgan and Stoebe [13], the electron traps have not been so far identified (see the recent review by Lakshmanan [14]). RE 3+ activators have been originally proposed as the electron traps, i.e.…”
Section: X-ray Induced Tslmentioning
confidence: 99%
See 1 more Smart Citation
“…− with the release of an electron upon irradiation and these ions are stabilised by a nearest neighbour Ca vacancy [3]. The decrease of τ 1 upon irradiation may be due to the release of these free electrons near to Ca vacancy sites.…”
Section: Somentioning
confidence: 99%
“…Besides thermoluminescense (TL), other methods like TL emission spectra, Photoluminescence (PL), Optical absorption (OA), Electron Spin resonance (ESR) are commonly used for the identification of lattice defects. Though a variety of defect centres are reported in sulphate based phosphors, Morgan and Stoebe [3] reported that 4 …”
mentioning
confidence: 99%